Biomarkers of bone disease in persons with haemophilia. Issue 1 (27th August 2020) - Goldscheitter, Galen; Recht, Michael; Sochacki, Paul; Manco‐Johnson, Marilyn; Taylor, Jason A.
Abstract: Introduction: Persons with haemophilia (PwH) have abnormally low bone density and increased risk of fractures. We previously demonstrated decreased skeletal health in factor VIII (FVIII)‐deficient mice. Thus, we hypothesized factor deficiency is an independent risk factor for decreased skeletal health. Aim: We seek to identify differences in bone‐related cytokine expression among PwH and healthy controls. Methods: We evaluated plasma samples from 79 participants with severe FVIII deficiency and 51 age‐matched healthy controls. Plasma samples were assessed for RANKL and OPG, cytokines that regulate bone metabolism, and CTX‐1, a biomarker for bone resorption, as well as 10 bone‐related cytokines. Results: CTX‐1 is higher among samples from FVIII‐deficient participants compared to controls ( P  < .01) but not among participants with recent factor use (within 24 hours of sample collection) ( P  = .21). Among PwH greater than 16 years of age (PwH ≥ 16), OPG is increased with recent factor use ( P  < .01) but not without ( P  = .34). Lower levels of TNF‐α ( P  < .01), interleukin (IL)‐12 ( P  < .01) and IL‐10 ( P  < .001) were found among samples from PwH. Controlling for subject age, IL‐12 and IL‐10 levels are lower in PwH ≥ 16 ( P  < .01, P  < .001) but not PwH under 16 (PwH < 16) ( P  > .05). Levels of TNF‐α were lower among PwH < 16 only ( P  < .05). These differences are not observed in participants with recent factor use. Conclusions: In PwH, markers of bone metabolism and circulating cytokine levels are abnormal. Recent factor use reverses many of these differences suggesting FVIII replacement ameliorates this pathology. This study suggests bone disease present in PwH is intrinsic to FVIII deficiency.